(-12)+(-6)÷2-[(-5)of(-4)-{2-(3-5)}]
Answers
Answered by
3
Heya!!
Here's your answer
______________________
( - 12 ) + ( - 6 ) ÷ 2 - [ ( - 5 ) ( - 4 ) - { 2 - ( 3 - 5 ) } ]
= - 12 - 3 - [ - 20 - { 2 + 1 } ]
= - 15 - [ - 20 - 3 ]
= - 15 - ( - 23 )
= - 15 + 23
= + 8
[ • Using BADMAS identity ]
__________________________
Hope it helps you dear!
★ Devil king
Here's your answer
______________________
( - 12 ) + ( - 6 ) ÷ 2 - [ ( - 5 ) ( - 4 ) - { 2 - ( 3 - 5 ) } ]
= - 12 - 3 - [ - 20 - { 2 + 1 } ]
= - 15 - [ - 20 - 3 ]
= - 15 - ( - 23 )
= - 15 + 23
= + 8
[ • Using BADMAS identity ]
__________________________
Hope it helps you dear!
★ Devil king
bmusha:
but answer was -31
Answered by
4
I hope it's help you
Attachments:
![](https://hi-static.z-dn.net/files/d8e/19f85b62b18cde61329442303920a2e1.jpg)
Similar questions
Biology,
8 months ago
Hindi,
8 months ago
English,
8 months ago
Environmental Sciences,
1 year ago
Math,
1 year ago